Preparation of solution processed photodetectors comprised of two-dimensional tin(ii) sulfide nanosheet thin films assembled via the Langmuir–Blodgett method. Issue 43 (6th August 2021) - Norton, Kane; Jacobs, Janet; Neilson, Joseph; Hopkinson, David; Mokhtar, Mohammad Z.; Curry, Richard J.; Lewis, David J.
Abstract : Norton et al . report the manufacture of fully solution processed photodetectors based on two-dimensional tin(ii ) sulfide assembled via the Langmuir–Blodgett method. Abstract : We report the manufacture of fully solution processed photodetectors based on two-dimensional tin(ii ) sulfide assembled via the Langmuir–Blodgett method. The method we propose can coat a variety of substrates including paper, Si/SiO2 and flexible polymer allowing for a potentially wide range of applications in future optoelectronic devices.